SpToll1 and SpToll2 modulate the expression of antimicrobial peptides in Scylla paramamosain. (October 2018) - Chen, Yan; Aweya, Jude Juventus; Sun, Wanwei; Wei, Xiaoyuan; Gong, Yi; Ma, Hongyu; Zhang, Yueling; Wen, Xiaobo; Li, Shengkang
Abstract: Tolls and Toll-like receptors (TLRs) were the first pattern recognition receptors (PRRs) identified to play key roles in host innate immunity. However, relatively little is known about other types of Toll-like receptors in Scylla paramamosain, although a Toll-like receptor ( Sp Toll1) has recently been cloned. In this study, we cloned and characterized another novel Toll-like receptor 2 ( Sp Toll2) from S. paramamosain . The full-length cDNA of Sp Toll2 is 3391 bp with a 2646 bp open reading frame (ORF) encoding a putative protein of 881 amino acids, and predicted to contain six extracellular leucine-rich repeat (LRR) domains, a transmembrane domain and an intracellular Toll/IL-1 receptor (TIR) domain. Phylogenetic analysis revealed that Sp Toll2 clustered with Drosophila Toll1, and shared high homology with Pt Toll4. Real-time qPCR analysis showed that Sp Toll2 was widely expressed in all tissues tested, with the highest level found in hemocytes and hepatopancreas while the lowest in heart and muscle. The transcript levels of both Sp Toll1 and Sp Toll2 in mud crabs hemocytes was induced following challenge with Vibrio parahaemolyticus, Staphylococcus aureus, Polyinosinic: polycytidylic acid (Poly I:C) and white spot syndrome virus (WSSV). In addition, recombinant Sp Toll1-LRR and Sp Toll2-LRR proteins could bind to V. parahaemolyticus, S. aureus, Escherichia coli, and Beta Streptococcus . In order to study the signaling pathway of AMPs' expression in mud crab, RNA interference were used to test the expression of Sp AMPs after the challenges with V. parahaemolyticus or S. aureus . The data suggested that Sp Toll1and Sp Toll2 could regulate the transcripts of several AMPs and four immune related mediators ( Sp MyD88, Sp Tube, Sp Pelle and Sp TRAF6) at different scale. While silencing of Sp Toll1 post pathogens challenge attenuated the expression of Sp Histin, Sp ALF1 and Sp ALF5 in mud crab's hemocytes, depletion of Sp Toll2 post pathogens challenge inhibited the expression of Sp ALF1-6, Sp GRP, Sp Arasin and Sp Hyastastin. Furthermore, the results of overexpression assay also showed Sp Toll1 and Sp Toll2 could enhance the promoter activities of Sp ALFs in mud crab. Taken together, these results indicated that Sp Toll1 and Sp Toll2 might play important roles in host defense against pathogen invasions in S. paramamosain. Highlights: Full-length of Sp Toll2 with 3391 bp was isolated from mud crab. Sp Toll1 and Sp Toll2 showed strong binding bacterial activities. Sp Toll1 and Sp Toll2 regulated the expression of AMPs and downstream mediators.